Oral field cancerization: an update on current concepts - Meenakshi Mohan; Nithya Jagannathan (Frontiers Media S.A., 2014)
There always exists a field with genetically altered cells with a high risk of developing premalignant and malignant lesions. It may often happen that an individual stem cell is genetically altered and can cause the formation of a clone or a patch which is likely to turn into a tumor. This explains the higher recurrence rates following tumor resections. It is essential to identify and to treat this field in order to have greater chances to prevent cancer and achieve a better outcome. This article reports concepts, theories and markers for the assessment of field cancerization.